Protecting All Children's Teeth (PACT): Oral Health Screening - Melinda Clark; David Krol (Association of American Medical Colleges, 2013)
Abstract This lecture-based resource reviews the American Academy of Pediatrics policy on risk assessment and screening, explains how pediatricians can assess dental caries risk in their patients, present a tool that can be used to assist in risk assessment, and proposes referral options for patients deemed at risk. This resource is a part of Protecting All Children's Teeth (PACT), a series created by the American Academy of Pediatrics' Oral Health Initiative to educate medical students, residents, pediatric primary care providers, and others interested in infant, child, and adolescent health about the importance of oral health in overall health. The series provides in-depth coverage of child oral health, oral health guidance, and preventive care to increase comfort in recognizing dental disease and conditions and communicating with dental professionals. This resource has been in use since 2007 by physicians in training at the medical school and residency levels, as well as those in clinical practice. The content has been used by pediatric, family medicine, and emergency medicine physician training programs, as well as by physician assistants, nurse practitioners, nurses, dentists, and dental hygienists in training and in clinical practice.